Effect of lighting illuminance and colour temperature on mental workload in an office setting - Jiayi Bao (Nature Portfolio, 2021)
Abstract The mental workload of subjects was tested under different lighting conditions, with colour temperatures ranging from 3000 to 6500 K and illuminance ranging from 300 to 1000 lx. We used both psychological and physiological responses for evaluation. The former was based on NASA Task Load Index (NASA-TLX, NASA), and the latter was based on the electroencephalogram (EEG) P3b analysis of event-related potentials using the “oddball” paradigm experimental task. The results show that as illuminance increases, and the response time becomes longer with a colour temperature of 3000 K (P < 0.01). However, when the colour temperature is set at 6500 K, the response time becomes shorter as the illuminance increases (P < 0.01). P3b amplitudes were significantly affected by colour temperature (P = 0.009) and illuminance (P = 0.038) levels. The highest amplitudes occurred at 3000 K and 750 lx, which is consistent with the trend shown by the subjective scale. The data analysis of error rates is not significant. These results suggest that an office environment with a colour temperature of 3000 K and illumination of 750 lx, which exerts the lowest mental workload, is the most suitable for working. However, the interaction between colour temperature and illuminance in affecting the mental workload of participants is not clear. This work provides more appropriate lighting choices with colour temperature and illuminance to reduce people’s mental workload in office settings.